Differential effects of crude oil on denitrification and anammox, and the impact on N2O production. (September 2016) - Ribeiro, Hugo; Mucha, Ana P.; Azevedo, Isabel; Salgado, Paula; Teixeira, Catarina; Almeida, C. Marisa R.; Joye, Samantha B.; Magalhães, Catarina
Abstract: Denitrification and anammox are key processes for reducing the external nitrogen loads delivered to coastal ecosystems, and these processes can be affected by pollutants. In this study, we investigated the effect of crude oil on denitrification and anammox. Controlled laboratory experiments were performed using sediment slurries from the Lima Estuary (NW Portugal). Anammox and denitrification rates were measured using 15 N-labeled NO3 −, and the production of 29 N2 and 30 N2 quantified by membrane inlet mass spectrometry. Results revealed that while denitrification rates were stimulated between 10 and 25 000 times after crude oil amendment, anammox activity was partially (between 2 and 5 times) or completely inhibited by the addition of crude oil when comparing to rates in unamended controls. Similar results were observed across four estuarine sediment types, despite their different physical-chemical characteristics. Moreover, N2 O production was reduced by 2–36 times following crude oil addition. Further work is required to fully understand the mechanism(s) of the observed reduction in N2 O production. This study represents one of the first contributions to the understanding of the impact of crude oil pollution on denitrification and anammox, with profound implications for the management of aquatic ecosystems regarding eutrophication (N-removal). Graphical abstract: Highlights: Denitrification rates were stimulated under crude oil treatments. Anammox activity was reduced by the addition of crude oil. Sediment characteristics seemed to affect processes rates under crude oil effect. Crude oil reduces nitrous oxide production despite the stimulation of denitrification. Crude oil addition stimulated denitrification rates but inhibited anammox activity and reduced N2 O production